Investigation of the formation mechanisms in high internal phase Pickering emulsions stabilized by cellulose nanocrystals - Miao, Chuanwei (Philos Trans A Math Phys Eng Sci, 2018)
Medium and high internal phase Pickering emulsions stabilized by cellulose nanocrystals (CNCs) have been prepared and the effects of CNC concentration and type of oil phase on the properties of emulsions were studied. The maximum oil phase volume that can be stabilized by CNCs is 87% when the CNC concentration is 0.6 wt.%; this slightly decreases to 83% when the CNC concentration is increased to 1.2 wt.% or higher. In addition, the oil droplets stabilized with 0.6 wt.% CNC suspensions have a larger size than those stabilized with higher concentration CNC suspensions. As evidenced by the change in oil droplet morphology and size, two different emulsion formation mechanisms are proposed. For a CNC concentration of 0.6 wt.%, the extra oil added into the emulsion is accommodated by the expansion of oil droplet size, whereas for CNC concentrations of 1.2 wt.% and higher, the oil is stabilized mainly by the formation of new oil droplets.